Spatial-temporal variation characteristics of cultivated land and controlling factors in the Yangtze River Delta region of China - Huo, Kun; Ruan, Yunfeng; Fan, Haizhou; Guo, Chunhui; Cai, Hong (Frontiers in Environmental Science, 2022)
Comprehending the change characteristics and controlling factors of regional cultivated land resources is one of the important preconditions for its healthy development. This study analyzed the spatial-temporal variations of characteristics of cultivated land resources and controlling factors in the Yangtze River Delta region. Thus, we used mathematical statistical, land use dynamic degree model, principal component analysis and geographically weighted regression model to analyze cultivated land area and social-economic development factors in the Yangtze River Delta region from 2009 to 2018. The results showed that the cultivated land and per capita cultivated land area had a decreasing trend from 2009 to 2018, decreased by 8.5×104 hectares and 0.0039 hectares. From the perspective of spatial pattern, the rapidly decreasing areas of cultivated land was mainly distributed in the southeast, while the slowly decreasing areas of cultivated land was concentrated in the northwest and the slowly increasing areas presented as scattered distribution, which was also the same spatial distribution for the per capita cultivated land area in the Yangtze River Delta region. Among these factors, population (POP) and the total power of agricultural mechanization (TPAM) had positive spatial correlation with cultivated land. GDP had negative spatial correlation with cultivated land, which revealed that cultivated land was in-tensely affected by human activities. Moreover, spatial distribution and influence degree of the controlling factors differed in regions. Our research is expected to reveal the relationship between economic development and cultivated land protection for providing references for strengthening regional cultivated land management, maintaining the healthy development of regional resources and rational utilization of cultivated land.